Improving Knowledge, Attitude, and Perception towards Childhood Diarrhea Using Interactive Discussion in Kulon Progo Community - Jarir At Thobari; Wahyu Damayanti; Asal Wahyuni Erlin Mulyadi; Jonathan Hasian Haposan; Annisa Setiyaningrum; Shofya Indraguna; Sutarman S; Nailatul Arifah; Anggit Dewi Rahayu; Faridatun Khasanah; Al Razi Sena; Yati Soenaro (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Introduction: Diarrhea is still a leading cause of death in the world in children, especially in children under 5 years. Diarrhea is a contagious disease with relatively high morbidity and mortality rates. Rotavirus is a cause of diarrhea in children and is a very important public health problem in both developed and developing countries. Parents' knowledge is one of the causes of diarrhea due to parents' ignorance of the causes of diarrhea, how diarrhea is transmitted and how to prevent diarrhea.Methods: This explanatory mixed qantitative-qualitative method with a quasi experimental design study to determine the effect of interactive discussion on changes in knowledge, attitudes, and perceptions towards the prevention and management of childhood diarrhea among mothers and children living in the area of The Ash-Shiddiqiyah Orphanage located in Central Sremo, Hargowilis, Kokap, Kulon Progo Regency, Yogyakarta.Results: The activities were conducted on November 29th, 2020 with 67 participants consisting of 54 children and 13 mothers from the area. The questionnaire results showed that the posttest scores in all sections (knowledge, attitudes, and perceptions) were significantly higher compared to the the pretest scores. There were increment of 1.33 points in knowledge (p<0.001), 0.5 points in attitudes (p<0.001),  0.4 points in perception (p<0.05), and 0.76 points in overall scores (p<0.001). Interviewees agreed that the intervention has been properly conducted with clear delivery, easy to understand for both adults and children, and ability to two-way communication. Technology utilization might help the understanding of the audience. Besides, a small group discussion in the session may benefit the participants to ask more confidently compared to asking in the middle of large group due to shame.Conclusion: Interactive discussion could be used to improve knowledge, atittude and perception towards childhood diarrhea. The delivery of interactive discussion using simple language for targetted population, adoption of small group discussion and technology utilization might help the effectiveness of the intervention. Further study is needed to identify effective ways to promote the childhood diarrhea management and prevention in community.